INDUCTION OF TRIPLOID SANDALWOOD PLANT (Santalum album L.) THROUGH ENDOSPERM CULTURE IN VITRO - Lazarus Agus (Pusbindiklat - LIPI, 2011)
Sandalwood (Santalum album L.) is an over exploitation that causes the population decreases drastically. An experiment was carried out to get triploid plant by using young seed culture. Young seeds of sandalwood were peeled and grew on solid Murashige and Skoog (MS) media formulation with or without addition hormones of α-napthaleneacetic acid (NAA), 2,4 dichlorophenoxyacetic acid (2,4-D), 6-benzylaminopurine (BA) or kinetin.(K). The young seed did not form shoot, but its endosperm formed callus. The endosperm produced callus 26.67% on media with addition of BA 1 mg/l, but not on media without any addition of hormone. The best callus production was on media with addition of NAA 2 mg/l and BA 1 mg/l. The best somatic embryos formation was NAA 1 mg/l + BA 1 mg/l and shoot formation was 2,4-D 1 mg/l + K 1 mg/l treatments. The resulted shoots from endosperms are expected to be triploid plants.